Sigma models of the AdS/CFT correspondence - Bykov, Dmitry Vladimirovich (Trinity College (Dublin, Ireland). School of Mathematics, 2011)
The thesis is dedieated to the investigation of the properties of particular two-dimensional quantum field theories, i.e. sigma-models with target space of the form AdS5 x S5γ and AdS4 x CP3. The main results of the thesis are as follows: 1. The leading finite size correction to the dispersion relation of a soliton solution of the AdS5 x S5γ sigma model has been calculated (γ is a parameter describing the deformation of the metric). Nontrivial dependence on γ has been found. ..
Keywords: Mathematics, Ph.D.; Ph.D. Trinity College Dublin.